Information Security in an Internet of Things Network Based on Blockchains and User Participation - Daniels, Anton (Luleå tekniska universitet, Institutionen för system- och rymdteknik, 2019)
The amount of connected Internet of Things devices has seen a large growth during the last couple of years and shows no signs of slowing down. Considering the momentum of the technological advancement in our society with new technologies such as blockchains, AI and machine learning, a large amount of issues could occur if not prevented beforehand, especially within security. Therefore this thesis will examine how to maintain the information security in an Internet of Things network based on blockchains and user participation, by taking an exploratory approach to create an understanding of the issues and possible solutions when implementing a network of this type. By using a case developed together with Luleå Kommun this thesis takes a qualitative approach to the research. This is done by using solutions to issues which appeared during the development of this implementation to draw a conclusion on how to maintain the information security in an Internet of Things network based on blockchains and user participation.